2021
DOI: 10.22392/actaquatr.801564
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and Heavy Metal Resistance of Escherichia coli Strains Isolated from the Seve Dam, and Konak Pond, Kilis, Turkey

Abstract: Pollution of surface waters with coliform bacteria having antibiotic and heavy metal resistance has become an increasing public health risk. For this reason, antibiotic and heavy metal resistance profiles of fecal microorganisms in surface water samples collected from two different points (Seve Dam and Konak Pond, Kilis, Turkey) were analyzed in this study. The various physicochemical parameters such as pH, Temperature, Total Dissolved Solids (TDS), Electrical Conductivity (EC) of samples were also examined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The presence of fecal coliforms in aquatic environments indicates the contamination of waters with the fecal material of man or other animals. Several previous studies have also demonstrated a higher concentration of total and fecal coliforms in different water bodies in Turkey (Buyukkaya Kayis et al 2017;Avsar 2018;Hulyar and Altug 2020;Mercimek Takcı et al 2021). Our another a study performed for different locations at same time in Kilis observed fecal streptococ contamination as 11 EMS/100 mL (Mercimek Takci and Toplar 2023).…”
Section: Resultsmentioning
confidence: 80%
“…The presence of fecal coliforms in aquatic environments indicates the contamination of waters with the fecal material of man or other animals. Several previous studies have also demonstrated a higher concentration of total and fecal coliforms in different water bodies in Turkey (Buyukkaya Kayis et al 2017;Avsar 2018;Hulyar and Altug 2020;Mercimek Takcı et al 2021). Our another a study performed for different locations at same time in Kilis observed fecal streptococ contamination as 11 EMS/100 mL (Mercimek Takci and Toplar 2023).…”
Section: Resultsmentioning
confidence: 80%
“…This might show that the main source of contamination in the Orontes River is domestic sewage and solid residues from surrounding densely populated areas. There are many reports on the existence of fecal coliforms in various aquatic environments in Turkey [19][20][21]. The highest total coliform and fecal coliform levels were reported to be 13x10 highlighted that indicated the uncontrolled discharges with 940x10 3 CFU/100 mL total coliform value at Alibeykoy Creek [23].…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect of this manuscript is the determination of antibiotic susceptible pro les in Gr negative bacteria isolated from the Alleben water sample. Although the prevalence of antibiotic-resistant bacteria (ARB) in many freshwater sources of Turkey has been previously demonstrated [32][33], this is the rst study that indicated the high frequency of resistance in the surface waters of Alleben, Gaziantep.…”
Section: Discussionmentioning
confidence: 99%